Building a Sales Information System as an effort to create Efficiency in Customer Service at Omah'e Cinta Art and Gallery - Nugroho Widianto (Peneliti.net, 2023)
Omah'e Cinta Art Gallery is a gallery that sells various products and types of women's clothing. At this time the sales system at Omah'e Cinta Art Gallery is still conventional. So that the process of ordering clothes and the process of making orders reports are less efficient. To be able to reach more customers and expand the marketing area as well as gallery promotion, media is needed that can optimally support promotional activities, sales transactions and gallery information. One of the media that is of concern to the public today is to use online media websites. The purpose of this research is to produce a sales information system that can solve problems and simplify the process of selling services to consumers. Building a sales information system for Omah'e Cinta Art Gallery using the programming language PHP and MySQL as the data base. The system development method uses the waterfall method and the system approach method where the object approach method uses several tools such as use cases, use case scenarios, and activity diagrams. Furthermore, qualitative analysis is used to prove whether or not the role of the Sales Information system is in an effort to create Efficiency in Customer Service. The successful development of a web-based sales information system can be a solution in an effort to improve service to consumers to be more effective and efficient.